Enhancing the therapeutic activity of hyperimmune IgG against chikungunya virus using FcγRIIIa affinity chromatography - Fox, Julie M.; Roy, Vicky; Gunn, Bronwyn M.; Bolton, Glen R.; Fremont, Daved H.; Alter, Galit; Diamond, Michael S.; Boesch, Austin W. (Frontiers in Immunology, 2023)
Introduction Chikungunya virus (CHIKV) is a re-emerging mosquito transmitted alphavirus of global concern. Neutralizing antibodies and antibody Fc-effector functions have been shown to reduce CHIKV disease and infection in animals. However, the ability to improve the therapeutic activity of CHIKV-specific polyclonal IgG by enhancing Fc-effector functions through modulation of IgG subclass and glycoforms remains unknown. Here, we evaluated the protective efficacy of CHIKV-immune IgG enriched for binding to Fc-gamma receptor IIIa (FcγRIIIa) to select for IgG with enhanced Fc effector functions. Methods Total IgG was isolated from CHIKV-immune convalescent donors with and without additional purification by FcγRIIIa affinity chromatography. The enriched IgG was characterized in biophysical and biological assays and assessed for therapeutic efficacy during CHIKV infection in mice. Results FcγRIIIa-column purification enriched for afucosylated IgG glycoforms. In vitro characterization showed the enriched CHIKV-immune IgG had enhanced human FcγRIIIa and mouse FcγRIV affinity and FcγR-mediated effector function without reducing virus neutralization in cellular assays. When administered as post-exposure therapy in mice, CHIKV-immune IgG enriched in afucosylated glycoforms promoted reduction in viral load. Discussion Our study provides evidence that, in mice, increasing Fc engagement of FcγRs on effector cells, by leveraging FcγRIIIa-affinity chromatography, enhanced the antiviral activity of CHIKV-immune IgG and reveals a path to produce more effective therapeutics against these and potentially other emerging viruses.